SPE Western Regional Meeting 2015
DOI: 10.2118/174034-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applying Machine Learning Techniques to Interpret Flow Rate, Pressure and Temperature Data From Permanent Downhole Gauges

Abstract: Permanent downhole gauges (PDGs) provide a continuous record of pressure, temperature, and sometimes flow rate during well production. The continuous record provides us rich information about the reservoir and makes PDG data a valuable source for reservoir analysis. It has been shown in previous work that the convolution kernel based data mining approach is a promising tool to interpret flow rate and pressure data from PDGs. The convolution kernel method denoises and deconvolves the pressure signal successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Numerous researches has been conducted to interpret flow rate and pressure data using machine learning approaches for different applications. Notably, studies about the interpretation of pressure and flow rate data collected from permanent downhole gauge (PDG) has been done by researchers for well test analysis using machine learning [9,11,12,14]. The results of the studies demonstrated that machine learning is capable of extracting relationship between the parameters in the data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researches has been conducted to interpret flow rate and pressure data using machine learning approaches for different applications. Notably, studies about the interpretation of pressure and flow rate data collected from permanent downhole gauge (PDG) has been done by researchers for well test analysis using machine learning [9,11,12,14]. The results of the studies demonstrated that machine learning is capable of extracting relationship between the parameters in the data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linear regression is a computationally fast algorithm with high interpretability through weightage of each feature on the output. Each term within the features reflects the physical properties of flow rate in relation with pressure and time [11]. The features were formulated by mapping the flow rate based on pressure convolution was shown in Eq.1 [9].…”
Section: Linear Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods use the pressure data from the PDG as the only data to identify transients because the flow rate is not always measured in line with pressure or may have a much lower sampling rate. Even though there are some data analysis and machine learning applications based on PDG data published, for example in [14][15][16][17], these studies were usually not concentrated on transient identification problem itself. For a clear understanding of the characteristics of each reviewed method, the terminology is first summarized using previous statements found in the literature and the terms of a 'transient' and a 'break point' are introduced.…”
Section: Introductionmentioning
confidence: 99%